2021
DOI: 10.3390/ijerph18137029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Frequency of Sweetened Beverages Consumption among Adults in Poland

Abstract: Background: in the context of the ongoing obesity epidemic and increase in cases of metabolic disorders among the population, it is significant, from the health, nutritional, and economic point of view, to a look at the habits of sugar-sweetened beverage (SSB) consumption of adults in Poland. This study aims to determine the sweetened beverages, which are the most popular and most frequently consumed by Polish consumers in correlation with sex, age, income, and education of the studied group of adults. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A cross-sectional study conducted on 1138 college students showed that 68% of men consumed sugary drinks daily compared to 55% of women, and the sugary drinks included fruit juices, milk, soft drinks, and energy drinks [ 50 ]. Another study conducted among Polish adults showed that the consumption of sugar-sweetened beverages was higher among men than among women [ 51 ]. Data obtained from the Chinese National Survey among children and adolescents aged 6–17 years observed that children and adolescents with high physical activity had a higher consumption of sugar-sweetened beverages than those without, and a higher consumption of sugar-sweetened beverages was associated with abdominal obesity but not general obesity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted on 1138 college students showed that 68% of men consumed sugary drinks daily compared to 55% of women, and the sugary drinks included fruit juices, milk, soft drinks, and energy drinks [ 50 ]. Another study conducted among Polish adults showed that the consumption of sugar-sweetened beverages was higher among men than among women [ 51 ]. Data obtained from the Chinese National Survey among children and adolescents aged 6–17 years observed that children and adolescents with high physical activity had a higher consumption of sugar-sweetened beverages than those without, and a higher consumption of sugar-sweetened beverages was associated with abdominal obesity but not general obesity [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to age, differences in the frequency of consumption of such products are also observed depending on education and financial situation. People with lower than secondary education, and those with very good or good financial status prevail [7]. The meta-analysis conducted by Alonso-Diego G. et al revealed that globally, over half of the participants had consumed energy drinks at some point in their lives.…”
Section: Introduction and Objectivementioning
confidence: 99%